Call centers and the modern individual - Dagohoy, Princess Diane H. (2007)
This ethnographic study explored how working as a call center agent influenced the identity, shaped communicative styles, and affected the work ethics of an individual. The call center phenomenon was taken as a consequence of modernity in which individuals are subject to respond. Qualitative methods of research were used such as focus interviews and participant observation. Using macro and micro perspectives in analyzing the consequences of modernity, the study concludes that rather than seeing the individual as passive and restrained by the changes brought by modernity, the study presents an individual who is rational and goal-oriented; whose identity is dynamic, fluid and capable of adapting and adjusting.